MODEL SALES TERRITORY MANAGEMENT “CLUSTER WAR” SEBAGAI BENTUK STRATEGI PEMASARAN PADA PT. TELKOMSEL SUB BRANCH MALANG - Rahmad Fajar; DR. Noermijati SE., MTM (Jurnal Ilmiah Mahasiswa FEB, 2012)
Abstract: This study aims to describe the application of models of Sales Territory Management (STM) "Cluster War" on PT. Telkomsel Sub Branch Malang which includes pre-implementation and implementation of STM. This study is expected to provide input for the purposes of education, especially in the field of marketing and can be used as a reference for other researchers who want to examine more deeply. Informants of this study is the SPV and Outlet Sales Operation PT. Telkomsel Sub Branch Malang as a key person, a staff Outlet Sales and Operations, as well as an Outlet Management Reseprentative (OMR). This type of research is descriptive qualitative approach and data collection techniques using in-depth interviews were guided by observation and documentation. The results illustrate that the sales territory management as a marketing strategy. Meanwhile, as a model of sales territory management (STM) "Cluster War" performed by five steps: mapping, classification outlet, perencnaan journey, kanvassing, periodic evaluation and monitoring which is required to perform in-depth analysis before implementation so that later formed the patterns and models desired. Keywords : Sales, Sales Territory Management